The Effectiveness of a Training Program in Developing Awareness of Certain Nonverbal Communication Skills among a Sample of Secondary School Female Students - Al-Aati, Hudaa Mahmoud Naji; Aqoub, Aiada Masoud (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The aim of the research was to identify the effectiveness of a training program designed to enhance awareness of certain nonverbal communication skills among a sample of high school female students. This was achieved by examining the differences between the scores of the experimental group and the control group before and after the implementation of the program. Additionally, the study aimed to assess the improvement in the scores of the experimental group after the program's conclusion. To accomplish this, an experimental methodology was employed, using a non-verbal communication scale applied to a sample consisting of 28 students, divided into two groups: 14 students in the experimental group and 14 in the control group. The results indicated that the training program was effective in enhancing nonverbal communication skills among the students. The findings revealed no statistically significant differences between the scores of the experimental and control groups in the pre-test of non-verbal communication skills. However, there were statistically significant differences in the scores of the experimental group between the pre- and post-tests, indicating the impact of the training program. Conversely, the control group showed no statistically significant differences between the pre- and post-tests. Finally, significant differences were found between the scores of the experimental and control groups in the post-test, confirming the effectiveness of the program in improving nonverbal communication skills among the students Keywords: communication, non-verbal, skills, and training.
Keywords: Communication; Nonverbal; Skills; Training